Knowledge on sexual and reproductive health among adolescents in a college at Seremban, Negeri Sembilan. - , Muhammad Firdaus Ujang; , Rosnah Sutan (Universiti Kebangsaan Malaysia, 2014)
Prevalence of adolescents involved in sexual and reproductive problems is on rise and it was associated with its knowledge. Several factors found to be associated with the knowledge and various sources of knowledge are chosen by adolescents for this information. Thus, this study was to determine the knowledge score, its influencing factors and the preference of the sources of knowledge.A cross-sectional study was done using adopted questionnaire involving 330 respondents aged 18 and 19 years old in Kolej MARA Seremban selected by simple random sampling. They were gathered in the halls and 338 adolescents from 454 students consented to involve in this study. Selfadministered questionnaire was used whereby a correct response was given a score of 2, 0 for an incorrect response and 1 for an answer of don’t know. Total score for all correct answers was 42. Descriptive analysis, bivariate and multivariate analysis was done in the analysis.The mean knowledge score was 37.32 (±2.967) with a significant difference for gender. Internets were the most common and preferred sources of the knowledge among them. There was 5.2% of them had heard on SMS intervention and 37.0% of them disagreed on SMS intervention.The result showed that the knowledge score was lower in males than females and internets were the most preferred source of the knowledge. Thus, interventions for knowledge improvement should be more on male adolescents.